2022
DOI: 10.1111/acel.13610
|View full text |Cite
|
Sign up to set email alerts
|

Role of sleep quality in the acceleration of biological aging and its potential for preventive interaction on air pollution insults: Findings from the UK Biobank cohort

Abstract: Sleep has been associated with aging and relevant health outcomes, but the causal relationship remains inconclusive. In this study, we investigated the associations of sleep behaviors with biological ages (BAs) among 363,886 middle and elderly adults from UK Biobank. Sleep index (0 [worst]–6 [best]) of each participant was retrieved from the following six sleep behaviors: snoring, chronotype, daytime sleepiness, sleep duration, insomnia, and difficulties in getting up. Two BAs, the KDM‐biological age and Pheno… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 49 publications
(97 reference statements)
1
24
1
Order By: Relevance
“…Our study implemented a natural quasi-experiment to indicate that short-term PM 2.5 exposure could accelerate the speed of biological aging captured by DNA methylation changes. Furthermore, given our study sheds some light on the potential mediator roles of the circulating biomarkers especially inflammation and oxidative stress, interventions with anti-inflammation medications, , sleep quality, or antioxidant supplements are worthwhile to be explored to figure out a relatively affordable and practical way to protect the public against the adverse aging effects of PM 2.5 . Future studies with larger sample sizes and multiple personal interventions on the effects of air pollution, as well as more precision measures of biological aging, are recommended to move this environmental aging topic forward.…”
Section: Discussionmentioning
confidence: 99%
“…Our study implemented a natural quasi-experiment to indicate that short-term PM 2.5 exposure could accelerate the speed of biological aging captured by DNA methylation changes. Furthermore, given our study sheds some light on the potential mediator roles of the circulating biomarkers especially inflammation and oxidative stress, interventions with anti-inflammation medications, , sleep quality, or antioxidant supplements are worthwhile to be explored to figure out a relatively affordable and practical way to protect the public against the adverse aging effects of PM 2.5 . Future studies with larger sample sizes and multiple personal interventions on the effects of air pollution, as well as more precision measures of biological aging, are recommended to move this environmental aging topic forward.…”
Section: Discussionmentioning
confidence: 99%
“…Not even a few published studies are there on KDM-biological age in relation to PM 2.5 . Gao et al 12 analyzed 363,886 middle and elderly adults with exposure to PM 2.5 from the UK Biobank and found that increased IQR of PM 2.5 concentrations was associated with KDM-biological age acceleration in people with high, medium, and low sleep indices but did not directly investigate the association between PM 2.5 and KDM-biological age acceleration. In addition, previous studies on other aging biomarkers provided additional evidence.…”
Section: Interpretations and Comparisons With Other Studiesmentioning
confidence: 99%
“…Therefore, a more in-depth study based on a comprehensive assessment of organismal aging has been conducted. A lasted study revealed an association between long-term PM 2.5 exposure and the Klemera–Doubal method (KDM)-biological age, which measures the aging of the body by incorporating biomarkers of several systems, such as the heart, liver, lung, immunological, and kidney. , As opposed to a single aging biomarker, this measure enabled it to compensate for the heterogeneity of aging in various body cells and fully capture the systemic aging of the body . Importantly, recent research has identified not only different rates of aging between individuals but also the existence of different individual aging molecules and different aging pathways, suggesting that aging may present organ and system differences .…”
Section: Introductionmentioning
confidence: 99%
“…A , light alcohol consumption (Liang et al, 2022), moderate coffee consumption (Enroth et al, 2015), good sleep quality (Gao et al, 2022), vitamin D supplementation (Vetter et al, 2022), and Mediterranean diet adherence (Esposito et al, 2022).…”
Section: Factors Associated With a Slower Aging Clock In Humansmentioning
confidence: 99%